2018
DOI: 10.1176/appi.ajp.2017.17040442
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Association of Amyloid Beta and Anxious-Depressive Symptoms in Cognitively Normal Older Adults

Abstract: Higher amyloid beta burden was associated with increasing anxious-depressive symptoms over time in cognitively normal older individuals. Prior depression history was related to higher but not worsening symptom ratings. These results suggest a direct or indirect association of elevated amyloid beta levels with worsening anxious-depressive symptoms and support the hypothesis that emerging neuropsychiatric symptoms represent an early manifestation of preclinical Alzheimer's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
112
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 198 publications
(138 citation statements)
references
References 37 publications
16
112
1
2
Order By: Relevance
“…Affective symptoms in subjective cognitive decline show increased risk of progression to mild cognitive impairment and dementia, suggesting the subthreshold symptoms of depres-sion as a possible manifestation of preclinical Alzheimer disease in these people. 40,41 Conversely, our analyses in a subgroup with cerebrospinal fluid biomarkers showed that the association between white matter hyperintensities and depressive symptoms is not influenced by Alzheimer disease pathology. To investigate whether factors other than white matter hyperintensity and Alzheimer disease pathology could explain these results, research in other cohorts is needed to provide more evidence.…”
Section: J Psychiatry Neurosci 2019;44(4)mentioning
confidence: 57%
“…Affective symptoms in subjective cognitive decline show increased risk of progression to mild cognitive impairment and dementia, suggesting the subthreshold symptoms of depres-sion as a possible manifestation of preclinical Alzheimer disease in these people. 40,41 Conversely, our analyses in a subgroup with cerebrospinal fluid biomarkers showed that the association between white matter hyperintensities and depressive symptoms is not influenced by Alzheimer disease pathology. To investigate whether factors other than white matter hyperintensity and Alzheimer disease pathology could explain these results, research in other cohorts is needed to provide more evidence.…”
Section: J Psychiatry Neurosci 2019;44(4)mentioning
confidence: 57%
“…These should include newer biomarkers, as guided by fundamental scientific insights. An amyloid-PET-based study has yielded similar results (i.e., showing no clear link with amyloid pathology) when evaluating hippocampal atrophy in a cohort of depressed people and matched controls (De Winter et al, 2017), even though others have pointed out that amyloid-positive individuals do have a tendency to progressively manifest more neuropsychiatric symptoms (Harrington et al, 2017;Donovan et al, 2018). It is clear that further research efforts could and should use the newer antemortem diagnostic techniques (e.g., LP and/or PET) to add to these findings.…”
Section: Results Are Listed Inmentioning
confidence: 96%
“…Other studies have shown that subjects with depression have a higher incidence of MCI (Muller et al, 2007;Ng et al, 2009). Depressive patients have more amyloid abnormalities than non-depressive patients (Donovan et al, 2018) MCI with Aβ burden of the brain is associated with an increased risk of having neuropsychiatric symptoms (Krell-Roesch et al, 2019). Individuals with MCI are at an increased risk of progression to more severe cognitive impairment (Mitchell and Shiri-Feshki, 2009) and can have subtle impairments in everyday functioning (Hughes et al, 2012) and co-occurring depressive symptoms (Byers and Yaffe, 2011).…”
Section: Patients Have Higher Rates Of Depressionmentioning
confidence: 99%